PTH-033 Lumen-apposing fully covered self-expanding metal stent versus double pigtail plastic stents for endoscopic ultrasound guided transmural drainage of pancreatic fluid collections. (17th June 2017) - El-Sherif, Y; Courtney, K; Cannon, M; Lewis, D; Devlin, J
Abstract : Introduction: Endoscopic ultrasound guided transmural drainage (EUD) of pancreatic fluid collections (PFCs) (pancreatic pseudocyst and walled-off necrosis) is an established treatment. EUD has been primarily performed using cystotome and double pigtail plastic stents (DPS). More recently, the novel lumen-apposing fully covered self-expanding metal stents (LAMS) are increasingly preferred over DPS. Its efficacy, however, in terms of technical success rate and clinical outcomes has not yet been fully demonstrated. The aim of this retrospective cohort study is to compare the success rate, clinical outcomes and adverse events (AE) in EUD of PFC with DPS and LAMS. Method: Consecutive patients with symptomatic PFCs who underwent EUD between 2011 and 2016 were divided into two groups: (i) drainage using DPS, (ii) drainage using LAMS. Clinical outcomes in both groups were evaluated including the technical success rate, early AE (within 7 days), and late AE (within 3 months) of procedure. Cyst resolution was evaluated at 3 months post procedure. Results: 114 patients (35% female; mean age 51 years) underwent EUD. The aetiology of pancreatitis was gallstones (41%), alcohol (24.5%), idiopathic (24.5%), and miscellaneous causes (10%). Mean cyst size was 110 mm (30–220 mm). 89 patients underwent EUD using DPS, as compared to 25 using LAMS. The two groups were matched for age, sex and cyst size (p>0.05 for all). The overall technical success rate was 75% (86/114). On comparing both groups, successful stent placement was significantly higher in LAMS (92%), than with DPS (71%), p=0.03. Of those with attempted drainage by DPS, the stent could not be deployed in 26 patients (4=failed, 10=aspiration only, 12=track formation only). There was no significant difference between patients in the LAMS or DPS group in relation to intra-procedural complications (12% Vs 13%), early AE (4% Vs 10%) or late AE (16% Vs 8%), all p>0.05. Complete resolution of the PFCs was greater in the LAMS group as compared to the DPS group (92% Vs 80%) with fewer patients undergoing further intervention (8% Vs 20%), but this did not reach statistical significance, p=0.1. Conclusion: EUS-guided drainage of PFCs using LAMS is superior to DPS in terms of technical success rate. Early experience is suggesting higher resolution rates and less number of procedures required to achieve cyst resolution. Disclosure of Interest: None Declared